COMPARATIVE ANALYSIS OF EFFECTIVENESS AND SAFETY OF PHYTO- AND ANTIBIOTIC THERAPY OF ACUTE BRONCHITIS IN CHILDREN: RESULTS OF A MULTICENTER DOUBLE BLIND RANDOMIZED CLINICAL TRIAL - L. S. Namazova-Baranova (Pediatričeskaâ Farmakologiâ, 2014)
Although viruses cause most cases of acute bronchitis, antibacterial drugs are still widely used to treat children with such diseases; this results in development of antibiotic resistance. Therefore, one of the key objectives of clinical medicine is now an effort to reduce unreasonable use of antibacterial agents. A multicenter double blind randomized clinical trial (E-BRO-PCT) involved 182 2-6-years-old children and was aimed at assessing effectiveness and safety of phytotherapy (the syrup characterized by a fixed combination of thyme herb and ivy leaf extracts) of acute bronchitis. Patients were divided into groups according to the type of therapy: phyto-, antibacterial or multimodal therapy. The level of procalcitonin (PCT) – a bacterial inflammation marker – was measured retrospectively in the blood samples of all the children obtained at inclusion to the study. Therapy effectiveness was assessed by means of overall assessment of response to treatment on day 7. The share of children with low PCT and positive response to phytotherapy was comparable to the share of children subjected to antibiotic therapy. This is also true for all the patients included in the study regardless of the PCT level. Phyto- and antibacterial therapy featured a comparable safety profile; however, according to the researchers, the former one came out slightly better. Results of this study convincingly demonstrate that phytotherapy is an effective and well-tolerated type of treatment of acute bronchitis in children.